ATM and TP53 mutations show mutual exclusivity but distinct clinical impact in mantle cell lymphoma patients. Issue 6 (12th May 2019) - Mareckova, Andrea; Malcikova, Jitka; Tom, Nikola; Pal, Karol; Radova, Lenka; Salek, David; Janikova, Andrea; Moulis, Mojmir; Smardova, Jana; Kren, Leos; Mayer, Jiri; Trbusek, Martin
Abstract: Mantle cell lymphoma (MCL) is characterized by the hallmark t(11;14)(q13;q32) translocation, leading to cyclin D1 over-expression. Additionally, disrupting the DNA damage response pathway through ATM or TP53 defects plays an important role in MCL pathogenesis. Using deep next-generation sequencing we analyzed the mutual composition of ATM and TP53 mutations in 72 MCL patients, and assessed their impact on progression-free survival (PFS) and overall survival (OS). Mutated ATM and TP53 alleles were found in 51% (37/72) and 22% (16/72) of the cases examined, respectively, with only three patients harboring mutations in both genes. Only a mutated TP53 gene was associated with the significantly reduced PFS and OS and the same output was observed when ATM and TP53 defective groups included also sole deletions 11q and 17p, respectively. Determining the exact ATM/p53 pathway dysfunction may influence the selection of MCL patients for innovative therapies based on the targeted inhibition of selected proteins.